Evaluation of the acid-neutralizing capacity and other properties of antacids marketed in Morocco - Yafout, Mohamed; Elhorr, Hicham; Sbai El Otmani, Ibrahim; Khayati, Youssef (Medicine and Pharmacy Reports, 2021)
Aim. The aim of this study was to evaluate the acid-neutralizing capacity (ANC) and other properties of antacid drugs marketed in Morocco. Methods. Samples of 12 antacids were collected from pharmacies and were subjected to the test described in the US Pharmacopoeia in order to measure their ANC. Other properties such as price and sodium content were also studied. Results. All the tested brands met the minimal requirement of 5 mEq. However, Aluminum hydroxide/Magnesium hydroxide combinations showed a superior acid-neutralizing capacity over other products and oral suspensions showed better results compared to other pharmaceutical forms. Regarding the cost of antacids, Aluminum hydroxide/Magnesium hydroxide combinations and calcium carbonate/magnesium carbonate combinations showed the most favorable ANC/price ratio. Some of the antacids studied contain a high amount of sodium. Conclusion. All the antacids marketed in Morocco meet the USP requirement regarding their ANC. However, the ANC value should be included in the antacids’ labels so that both patients and physicians can choose the most appropriate product. The ANC value should be evaluated according to the dose of the active substance instead of the minimum labeled dosage in order to allow a better result interpretation.